Flowering and yield of Mat Rush (Juncus effusus L.) in response to population density, seedling size and transplanting date - SHEN Wei-qi; ZHANG Guo-ping; GUI Weng-guang; LU Cong-wu (浙江大学学报. 农业与生命科学版)
The response of Growth, flowering and yield in mat rush (Juncus effusus L.) to some cultural practices were studied. Planting density significantly affected stem number per hill (SPH), stem flowering percentage (SFP), long stem percentage (LSP), short stem percentage (SSP), biomass and economic yield. Higher density had significantly higher SPH at various stages and stem yield at harvest than lower density, and with an increase in planting density, LSP significantly decreased. There were no significant differences in SPH, SFP and yield between two seedling size treatments, indicating that even an offset with only three stems might be large enough to respond to environmental triggers for flowering. Delayed transplanting caused increased SFR. but had no significant effect on SPH, mean stem percentage (MSL), LSP, SSP, biomass and economic yield. It may be suggested that mat rush should be transplanted immediately after rice is harvested so as to reduce SFP and improve stem quality.